Evaluation of sudt formulation of hexaconazole for the control of powdery mildew disease of Hevea brasiliensis - Prem E E; Idicula S P; Jacob C K; Manju M J; Mushriff S K (Proceedings of the 15th Plantation Crops Symposium, PLACROSYM XV, 10-13 December 2002, Mysore .pp.572-575.)
Field experiments were conducted to evaluate a triazole fungicide, hexaconazole, for the management of powdery mildew disease of rubber (Hevea brasiliensis) caused by Oidium hevease Steinm. The experiment was conducted on a susceptible clone PB 5/51 in Cheruvally estate, Kottayam, Kerala and also in a disease-prone area on clone RRIM 600 in Vaikundam estate, Kanyakumari district, Tamil Nadu for seasons (1999 to 2002). Hexaconazole (2;) dust was evaluated as such and in alternate schedule with sulphur and in combination with recommended sulphur fungicide and at three concentrations. Results indicated that application of hexaconazole (2;) as such and in alternate schedule with sulphur was found to give better control. Combination of hexaconazole (2;) and sulphur and hexaconazole (1;) as such were observed to reduce powdery mildew disease. Alternate use of hexaconazole with sulphur is suggested to avoid the development of resistant strains.
Keywords: Disease control; Dust formulation; Hevea brasiliensis; Hexaconazole; Powdery mildew